Results management in the public sector: a critical reflection in the light of IPSAS - Barros, André Henrique Sousa; Matias-Pereira, José; Rodrigues, Jomar Miranda (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2025)
Purpose: To critically reflect on earnings management in the government context, focusing on the internationalization process of accounting standards for the public sector. The study aims to discuss the implications of the International Public Sector Accounting Standards (IPSAS) for earnings management in the public sector, considering the unique aspects and challenges present in the Brazilian context. Methodology: The theoretical framework was developed using integrative literature review techniques, with consultations conducted across the Scopus, Web of Science, SciELO, and SPELL databases. This review focused on three central themes: 1) earnings management in the public sector, 2) budget inaccuracy, and 3) IPSAS. Results: With the implementation of IPSAS and the pursuit of greater information comparability, Brazilian governments remain constrained by the legal requirements of budget compliance, as established by Law No. 4,320/64 and the Fiscal Responsibility Law (FRL) No. 101/2000. In this transitional phase to IPSAS, significant effects arise for earnings management. Adopting accrual-based accounting creates a paradox between enhanced information quality and manipulating accounting elements, particularly during electoral cycles. Contributions of the Study: By linking the adoption of IPSAS to earnings management, this essay opens a pathway for discussing management practices in international standards, providing a concise and temporally framed analysis of the respective adoptions.